"Ireland's economy in the 1980s: Stagnation and recovery": A Comment - McCarthy, F. Desmond (Economic & Social Studies, 1992)
During much of the 1980s the Irish national debt/GDP ratio reached 130 per cent, the current account deficit was over 15 per cent, while the government deficit remained persistently large. Since then the debt/GDP ratio has been reduced to close to 100 per cent, external accounts are in surplus, while the government deficit is now about 3 per cent of GDP. All this has entailed various costs with one of the more problematic being a rise and seeming persistence in unemployment.
Keywords: macroeconomics; Ireland; economic performance